(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Recurrence after repair of postoperative ventral hernias ranges from 15% to 55%, and forced closure of large defects may cause raised intra-abdominal pressure and abdominal compartment syndrome. Selecting a functionally tolerable volume of repair requires objective preoperative criteria rather than clinical estimation alone.